PENGARUH REFORMASI BIROKRASI DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI (Pada Kantor Pelayanan Pajak Kota Pratama Gorontalo) - Wiwin L Husin; Poppy Muzijat (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
Abstract The Effect Of Bureaucracy Reform And Employee Engagement On The Employee Performance At The Primary Taxservice Office, Gorontalo City This study aims to find out the effect of bureaucratic reform (X1) and employee engagement (X2) simultaneously on employee performance at the Gorontalo Primary Tax Service Office.The method used in this study is a quantitative approach with a descriptive presentation. Thedetermination of the population and the sampling technique used in this study is the censusmethod.The data collection techniques used are observation, interviews, questionnaires, anddocumentation.The analytical method in this studyis the path analysis method. The result of the first test shows that bureau craticre form (X1)and employee engagement (X2)simultan eously have a positive and significant effect on the employee performance at the Gorontalo Primary Tax Service Office by 0.801 or 80.1%. The resultof the second hypothesistesting indicates that bureaucratic reform (X1) partially has a positive and significant effecton the employee performance at the Gorontalo Primary Tax Service Office by 0.450 or 45%.The result of the third test demonstrates that employee engagement (X2) partially has apositive and significant effect on the employee performance at the Gorontalo Primary TaxService Officeby0.510 or51%. Keywords: Bureaucratic Reform, Employee Engagement ,Performance